SYNTHESIS OF SODALITE ZEOLITE FROM COAL BOTTOM ASH WITH VARIATION OF NaAlO2 CONCENTRATION USING ALKALI MELTING HYDROTHERMAL METHOD - Rahmatul Hanifah; Dwi Puryanti; Afdhal Muttaqin (Spektra: Jurnal Fisika dan Aplikasinya, 2018)
Synthesis of zeolites from bottom ash using alkali melting hydrothermal method with variation concentration of NaAlO2 solution had been done. Concentration of NaAlO2 solution was varied for 2,5 M (Z1), 2 M (Z2), 1,5 M (Z3) and 1 M (Z4). The bottom ash and NaOH are melted for 3 hours at 750C. Then, the sample is heated through a hydrothermal process with NaAlO2 crystallization medium. Then the sample is neutralized with aquades up to pH 9-10. Characterization of sample includes characterization zeolite type using of. The results of characterization using XRD show that the zeolite formed on samples Z1, Z2, and Z3 are zeolites of sodalite type and on Z4 sample of zeolite type are sodalit, nosean, and megakalsilit. The highest sodalite purity was obtained in Z3 sample, which is 73%.